2022
DOI: 10.3390/agriculture12020251
|View full text |Cite
|
Sign up to set email alerts
|

Use of Symbiotic Fungi to Reduce the Phytotoxic Effect of DCD Nitrification Inhibitors in Lettuce

Abstract: Nitrification inhibitors are commonly used to prevent nitrate leaching. However, the use of nitrification inhibitors is not free of side-effects. Some may be absorbed by the plant and cause phytotoxicity or even affect the food chain. Therefore, a solution that limits the absorption of nitrification inhibitors and its accumulation by the plant may mitigate health and environmental issues potentially associated with high levels of nitrification inhibitors. This solution may relay in the modulation of the plant’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…A study that describes the symptoms of TZ in plants has not been done so far. But the toxicity of NIs such as DCD including leaf chlorosis in clover (Macadam et al, 2003), lettuce (Padash et al, 2022) and 3,4-Dimethylpyrazole phosphate in clover have also been reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A study that describes the symptoms of TZ in plants has not been done so far. But the toxicity of NIs such as DCD including leaf chlorosis in clover (Macadam et al, 2003), lettuce (Padash et al, 2022) and 3,4-Dimethylpyrazole phosphate in clover have also been reported.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that the decrease in chlorophyll concentration is due to the effect of chlorophyllase, peroxidase and phenolic compounds and as a result of chlorophyll decomposition (Silva et al, 2007). The decrease in total chlorophyll content under DCD toxicity has been reported in lettuce plants (Padash et al, 2022). Also, the increase in carotenoid content under the side of nitri cation inhibitors can be related to the reduction of chlorophyll (Padash et al, 2022: Reeves et al, 1986.…”
Section: Total Chlorophyll and Cartenoidmentioning
confidence: 95%
See 3 more Smart Citations